Republic of Serbia : Eighth Review Under the Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Serbia's Eighth Review Under the Stand-By Arrangement. Notwithstanding some temporary supply shocks, economic activity remains robust, supported by recovery of private consumption and strong foreign direct investment. Significant fiscal over-performance has continued and efforts to address structural weaknesses have been accelerated. This, along with a healthy credit recovery on the back of substantial monetary policy easing, has helped support growth, while low inflation has reinforced recovery in real incomes. Continuing broader structural reforms are needed to improve the business climate and support Serbia's medium-term growth.